Penerapan Model Pembelajaran Berbasis Masalah dalam Mengembangkan Karakter Anak Usia Dini di TK AL-Islam Sleman Yogyakarta - Umayah, Siti (ACIECE, 2019)
Mass-based learning model is an appropriate method when applied to early childhoodeducation, in the application of this method can enhance development that can developchildren's creativity, children's independence, expand improvement, seek this research to find out the method applied. in this study researchers used a qualitative descriptive research method that collects research data using observation, interviews, document analysis and gathering conclusions. To analyze data, qualitative through data mining, data reduction, data transfer and conclusions draining. In this study itself, researchers obtained data involving teachers and principals, and in this study researchers as instruments of the research itself to obtain accurate data. From the results of research conducted in relation to learning methods based on problems that occur in early childhood that can be done in the learning process, discussed: Islamic, honest, sponsored, discipline, hard work, creative, independent, democratic and high curiosity. The application of problem based learning models is effective in developing character values in children